Overview of Indonesian Community Pharmacy: Understanding Practice Changes - Vinci Mizranita; Thellie Ponto; Beulah Sipana (Universitas Sebelas Maret, 2024)
Community pharmacy practice in Indonesia has shifted to a patient-centered model, offering a range of services that include treatment advice, chronic disease management, and public health promotion. This shift benefits consumers who visit community pharmacies as their initial healthcare point. The Indonesian healthcare system, a mix of public and private providers, is governed by a decentralized structure, fostering significant investment in private healthcare despite access limitations due to financial capacity. Medicines distribution, managed by the District Health Office, ensures supply to primary healthcare facilities, with community pharmacies regulated by the Ministry of Health and the Indonesian National Food and Drug Agency. Despite stringent regulations mandating comprehensive services, most pharmacists are not remunerated for their services. Pharmacy staff, including formally qualified pharmacists and pharmacy technicians, are registered professionals, with recent trends indicating a shift towards employing pharmacy technicians to enable pharmacists to focus on clinical roles. Economic factors and innovative service delivery modes, such as telepharmacy and online purchasing, are expected to influence future practices, enhancing the pharmacist's role in chronic disease management and other health conditions. The evolving community pharmacy practice in Indonesia reflects broader changes in the healthcare system and professional roles, with continued progression anticipated.